Cover Picture: Identification of Living Legionella pneumophila Using Species‐Specific Metabolic Lipopolysaccharide Labeling (Angew. Chem. Int. Ed. 5/2014). Issue 5 (17th January 2014) - Mas Pons, Jordi; Dumont, Audrey; Sautejeau, Grégory; Fugier, Emilie; Baron, Aurélie; Dukan, Sam; Vauzeilles, Boris
<x xml:space="preserve">Abstract</x> Legionella pneumophila is a deadly pathogen that was discovered after an outbreak in 1976 at the convention of the American Legion in Philadelphia. In their Communication on page 1275 ff., S. Dukan, B. Vauzeilles, and co‐workers describe a simple strategy to detect and identify living Legionella pneumophila by metabolic incorporation of a modified carbohydrate into their lipopolysaccharides, followed by further conjugation using click chemistry. Picture of Dr. Feely: CDC/Stafford Smith. Cover artwork: David Garino.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>